Occurrence and Control of Plant-parasitic Nematodes in Irrigation Water – A Review - Hugo, H.J.; Malan, A.P. Malan (South African Journal of Enology and Viticulture, 2016)
A literature study was carried out to determine what is currently known about the contamination of irrigation water with plant-parasitic nematodes, and what control measures are currently available. Contamination sources of irrigation water with plant-parasitic nematodes were investigated, including wells, boreholes, collected rainwater, ponds, lakes, dams, rivers, municipal water, runoff water, irrigation canals and drainage water in soilless culture. Only when the origin of irrigation water was a capped borehole was the risk of contamination with plant-parasitic nematodes low. The plantparasitic nematodes of economic importance to grapevine reported to be found in irrigation water were Meloidogyne spp., Xiphinema spp., Tylenchulus semipenetrans, Trichodorus sp., Criconemoides xenoplax and Pratylenchus spp. The different sampling techniques used for the detection and monitoring of plant-parasitic nematodes and the sampling time and location are listed. The survival and infection potential reported for each species of plant-parasitic nematode found in irrigation water was noted. Serious nematode parasites of grapevines, such as Meloidogyne javanica, can survive for 16 to 32 days, M. incognita, for up to 14 days, Pratylenchus, for up to 70 days, T. semipenetrans, for up to 128 days, and X. index, for up to 13 days in irrigation water. All reported techniques used for the management of nematodes in irrigation water are listed and possible future research into the control of plant-parasitic nematodes in irrigation water is discussed. From this review, substantial evidence was obtained of the danger of introducing plant-parasitic nematodes to grapevine production sites by means of irrigation water.